Effect of Lyophilization on the Physicochemical and Rheological Properties of Food Grade Liposomes That Encapsulate Rutin - Vega-Viveros, R; Osorio-Lira, F; Silva-Weiss, A; Gimenez-Castillo, B; Lopez-Polo, J (Elsevier Ltd, 2020)
The potential use of liposomes as carriers for food active ingredients can be limited by their physical and chemical instabilities in aqueous dispersions, especially for long-term storage. Lyophilization, a process commonly used in the food industry, can also be applied to stabilize and preserve liposomes and to extend their shelf-life. In this work, liposomes with potential use for designing functional foods were prepared with soy phospholipids and rutin. Homogenization and ultrasound were used for particle size reduction. Liposomal stability was evaluated by Dynamic Light Scattering, microscopy and rheological properties. Spherical and unilamellar liposomes were obtained in this work. Zeta potential (ξ = values were around −40 mV), which indicates a great suspension stability even for more than 30 days of storage. Rutin exerted a protective effect by both preventing damage to the liposome bilayer and maintaining the spherical structure after 56 days of storage. Lyophilization caused an increase in the size of the vesicles, reaching sizes around 419 nm and aggregation of vesicles with probably structural damage after 21 storage days. However, it helped to keep the rutin encapsulated (81.9%) for longer time, when compared to refrigerated liposomes. Rheological measurements showed, in general, that the power law model fitted most of the experimental results and dynamic rheological tests showed a sol-gel phase transition between 35 and 45 °C. Lyophilization caused a significant change in all evaluated rheological parameters. For the in vitro release tests, the liposomal bilayer acted as a barrier for the rutin release to the food simulating medium; therefore, the release rate of the antioxidant from the rutin encapsulated liposome was slow compared to the free rutin release rate. © 2019 Elsevier Ltd